Nurses’ perception of family tree-wellbeing - Suwarno Suwarno; Darunee Jongudomkarn (International Journal of Health Science and Technology, 2022)
Family Nursing is the nursing science branch that learns the nursing process, especially family health assessment (FHA). One of the items on FHA is the family tree wellbeing with five pictures that the family can choose based on their condition. The research was conducted in the Primary Care Unit, Bantul, Yogyakarta, in eight nurses. It employed a qualitative data research design with Focus Group Discussion were analyzed using coding, categorizing, and theme. The respondents said that family tree wellbeing assessment and symbols were easy to learn and straightforward, and it could be used to evaluate the family wellbeing conditions.